Mechanically Gated Ion Channels in Mammalian Hair Cells - Qiu, Xufeng; Müller, Ulrich (Frontiers in Cellular Neuroscience, 2018)
Hair cells in the inner ear convert mechanical stimuli provided by sound waves and head movements into electrical signal. Several mechanically evoked ionic currents with different properties have been recorded in hair cells. The search for the proteins that form the underlying ion channels is still in progress. The mechanoelectrical transduction (MET) channel near the tips of stereociliary in hair cells, which is responsible for sensory transduction, has been studies most extensively. Several components of the sensory mechanotransduction machinery in stereocilia have been identified, including the multi-transmembrane proteins TMHS/LHFPL5, TMIE and TMC1/2. However, there remains considerable uncertainty regarding the molecules that form the channel pore. In addition to the sensory MET channel, hair cells express the mechanically gated ion channel PIEZO2, which is localized near the base of stereocilia and not essential for sensory transduction. The function of PIEZO2 in hair cells is not entirely clear but it might have a role in damage sensing and repair processes. Additional stretch-activated channels of unknown molecular identity and function have been found to localize at the basolateral membrane of hair cells. Here, we review current knowledge regarding the different mechanically gated ion channels in hair cells and discuss open questions concerning their molecular composition and function.